FENOMENA SOSIAL EKONOMI PENYINTAS KELURAHAN LERE PASCA GEMPA DAN TSUNAMI - Hendra, Hendra; Laurang, Linda (Studi Budaya Nusantara, 2023)
This study explains how people live their lives by activating their remaining potential to survive the crisis that suddenly comes due to natural disasters, and definitely changes their lives. This study develops understanding from the perspective of adaptation and strategies that are unique to humans as cultural creatures. However, this study develops deeper by revealing the cultural acceleration of humans using/activating their potential in overcoming the crisis conditions that surrounded them at that time. Therefore, this study site is placed in community life after a natural disaster in Lere Village, West Palu District, Palu City. This study uses a case study approach by highlighting the post-tsunami phenomenon which only took place 1 year after 28 September 2018, with the aim of capturing people's memories and intentions in living life as survivors, which is still relatively new and well recorded. The results of the study show that the crisis faced by the driving community is a natural disaster, however, the way the community understands and develops its actions is very diverse and polyphonic. However, the cultural acceleration that is developed relies heavily on social, cultural conditions and material availability. This means that even though people are required/pressured to experience sudden and urgent conditions, they will continue to develop accelerated actions based on the conditions and phenomena they are living at that time, as a form of negotiation and compromise regarding their lives.